Validation of Tethya samaaii Ribeiro & Muricy, 2011, replacement name for the sponge Tethya rubra Samaai & Gibbons, 2005 (Demospongiae, Tethyida, Tethyidae) - Samaai, Toufiek; Gibbons, Mark J.; Muricy4, Guilherme (Zootaxa, 2017)
Tethya samaaii Ribeiro & Muricy, 2011 is a massive, irregularly globular or sub-spherical sponge with basal rooting processes or a disc-like attachment (Figure 1A). It was described from Oudekraal, on the west coast of South Africa as Tethya rubra Samaai & Gibbons, 2005 based on specimens collected during two surveys in 1996 (Samaai & Gibbons 2005). This species was later reported from Algoa Bay, on the southeast coast of South Africa by Waterworth et al. (2017).